Apakah pengendalian intern berpengaruh pada kualitas informasi laporan keuangan? - Wahyuni, Endang; Widodo, Sri (Journal of Business and Information Systems (e-ISSN: 2685-2543), 2019)
This research aims to determine the effect of accrual-based application, internal control, IT utilization and HR competency on the quality of financial statement information. The research is a quantitative approach with primary data source. The population in this research was 29 Organisasi Perangkat Daerah (OPD) of Sleman Regency. The sample in this research amounted to 107 respondents taken using a purposive sampling. Data collection in this research using a questionnare. The data analysis using a multiple regression. The result of this research show that the accrual-based application, IT utilization and HR competency have a positive effect on the quality of financial statement information, while internal control has no significant affect on the quality of financial statement information.